A Novel Hybrid Algorithm for Transient Near-Field Scattering from Rough Surface in 2-D Case. (26th August 2021) - Tian, Wei; Wei, Bing; Yang, Qian
Abstract : A novel hybrid algorithm is proposed to reduce the computation cost of the finite-difference time-domain (FDTD) method in calculating the transient near-field scattering from rough surface. The scattering problem is split into the FDTD calculation of equivalent sources on the contour enclosing rough surface and the calculation of the near-field radiation with the two-dimensional (2-D) time-domain Huygens' principle. The radiation fields are found from a surface integral of the temporal convolution for which the direct numerical integration of the convolution is computationally expensive. In this paper, the 2-D time-domain Green's function as the convolution kernel is approximated with a sum of exponential terms by using the Prony's method. Then, the semianalytical recursive convolution (SARC) approach is applied to complete the update of the near-field radiation. Compared with the traditional FDTD, this hybrid algorithm can significantly reduce the memory usage and run time, especially for the large distance between the rough surface and observation point.